Protection against avian coronavirus conferred by oral vaccination with live bacteria secreting LTB-fused viral proteins. Issue 5 (31st January 2022) - Lublin, Avishai; Katz, Chen; Gruzdev, Nady; Yadid, Itamar; Bloch, Itai; Farnoushi, Yigal; Simanov, Luba; Berkowitz, Asaf; Elyahu, Dalia; Pitcovski, Jacob; Shahar, Ehud
Highlights: Mucosal vaccination was shown particularly beneficial against respiratory viruses. An anti-IBV vaccine composed of three IBV polypeptides fused to LTB was designed. Vaccine composed of bacteria secreting polypeptides was orally delivered. Vaccine induced specific immune responses and shortened viral shedding duration. Abstract: The devastating impact of infectious bronchitis (IB) triggered by the IB virus (IBV), on poultry farms is generally curbed by livestock vaccination with live attenuated or inactivated vaccines. Yet, this approach is challenged by continuously emerging variants and by time limitations of vaccine preparation techniques. This work describes the design and evaluation of an anti-IBV vaccine comprised of E. coli expressing and secreting viral spike 1 subunit (S1) and nucleocapsid N-terminus and C-terminus polypeptides fused to heat-labile enterotoxin B (LTB) (LS1, LNN, LNC, respectively). Following chicken oral vaccination, anti-IBV IgY levels and cellular-mediated immunity as well as protection against virulent IBV challenge, were evaluated 14 days following the booster dose. Oral vaccination induced IgY levels that exceeded those measured following vaccination with each component separately. Following exposure to inactivated IBV, splenocytes isolated from chicks orally vaccinated with LNN or LNC -expressing bacteria, showed a higher percentage of CD8 + cells as compared to splenocytes isolated from chicks vaccinated with wild type or LTB-secreting E. coli and to chicks subcutaneously vaccinated. Significant reduction in viral load and percent of shedders in the vaccinated chicks was evident starting 3 days following challenge with 10 7.5 EID50 /ml virulent IBV. Taken together, orally delivered LTB-fused IBV polypeptide-expressing bacteria induced virus-specific IgY antibody production and was associated with significantly shorter viral shedding on challenge with a live IBV. The proposed vaccine design and delivery route promise an effective and rapidly adaptable means of protecting poultry farms from devastating IB outbreaks.